Impact of Surgery for Velopharyngeal Insufficiency on Eustachian Tube Function in Children: Pharyngeal Flap Versus Sphincter Pharyngoplasty. (November 2021) - Fuller, Colin; Brown, Kesley; Speed, Olivia; Gardner, James; Thomason, Ashlen; Dornhoffer, John; Johnson, Adam B; Hartzell, Larry
Objective: Velopharyngeal insufficiency (VPI) is a common speech disorder in patients with a history of cleft palate (CP) or 22q11.2 deletion syndrome. Pharyngeal flap (PF) and sphincter pharyngoplasty (SP) are 2 common surgeries to treat this disorder by decreasing unwanted nasal air emission and hypernasal resonance. Because Eustachian tube dysfunction (ETD) in patients with CP may be more frequent after surgery for VPI, we examined whether ETD was associated with either type of surgery. Design: Retrospective cohort study. Setting: Children's hospital-based tertiary referral center. Patients: A total of 225 children with VPI who underwent primary PF (201) or SP (24) between 2006 and 2017. Outcome measures: We examined differences in risk of ETD according to both surgical groups and proxies for postoperative nasal obstruction. These proxies included postoperative resonance measures and development of obstructive sleep apnea (OSA). Results: Both surgical groups had similar preoperative measures, except the PF group had higher hypernasality by PSA. Postoperatively, the PF group demonstrated lower hypernasal resonance by nasometry and PSA. There were no differences between PF and SP groups with regard to ETD. Proxies for postoperative nasal obstruction also were not predictive of postoperative ETD. Degree of CP and younger age were found to be risk factors for ETD. Conclusion: There was no significant difference in the effects of PF and SP on ETD in this study. Neither lower hypernasality nor incidence of OSA had any impact on ETD. Degree of CP and younger age were the only significant risk factors for ETD that this study identified.